2015
DOI: 10.1007/s11418-015-0922-8
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog/GLI-mediated transcriptional activity inhibitors from Crinum asiaticum

Abstract: The inhibition of the hedgehog (Hh) signaling pathway has emerged as an attractive anti-cancer strategy. As part of our continuing search for natural inhibitors of the Hh/GLI1 signaling pathway, we isolated three alkaloids (1-3) from Crinum asiaticum. Compounds 1 and 3 showed potent Hh/GLI1-mediated transcriptional inhibitory activity and exhibited cytotoxicity against human pancreatic (PANC1) and prostate (DU145) cancer cells. Our data revealed that compounds 1 and 3 clearly inhibited the Hh signaling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…Smo is released into cytoplasm to activate Gli nuclear translocation, which further initiates target gene transcription [ 23 ]. The transcription of anti-apoptotic factor Bcl2 was shown to be Gli-dependent [ 24 ]. Bcl2 stabilizes the membrane potential of mitochondria to reduce the release of cytochrome C [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smo is released into cytoplasm to activate Gli nuclear translocation, which further initiates target gene transcription [ 23 ]. The transcription of anti-apoptotic factor Bcl2 was shown to be Gli-dependent [ 24 ]. Bcl2 stabilizes the membrane potential of mitochondria to reduce the release of cytochrome C [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MTT assay was performed in order to estimate the toxicity of free or NC-formulated GlaB. Two different types of cell lines were selected for this study: non-stem cancer cells that contain a small CSC subpopulation (PANC1, human pancreatic carcinoma; SKOV3, human ovary adenocarcinoma; and GL261, murine glioma) [ 41–43 ] and pure glioblastoma-derived neural stem cells (GNS; patient-derived G7 human and engineered Ink4a/ARF, EGFRvIII overexpressed IENS murine) [ 31 ]. It is hypothesized that the GNS cell lines will be more sensitive to GlaB as they consist entirely of CSCs and therefore have a stronger dependence on the Hh pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that the genus Crinum belonging to the Amaryllidaceae family continue to yield alkaloids having interesting biological activities [ 13 , 30 ]. For example, galanthamine is used for symptomatic treatment of Alzheimer disease [ 31 ], crinine and 6‐ethoxybuphandrine exhibited anticancer effect [ 32 ], and cripowellin A, B, C, and D have antiplasmodial activity [ 33 ]. In the present study, 6-hydroxycrinamine and lycorine have been found in the bulb extract of C. abyscinicum , a plant which is important in Ethiopian traditional medicine [ 14 ].…”
Section: Discussionmentioning
confidence: 99%